1995
DOI: 10.1002/tea.3660320304
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between metaphors, beliefs, and actions in a context of science curriculum change

Abstract: This study is an interpretive investigation of Sarah, a first‐time teacher of middle‐ and high‐school science who, because of high levels of disruption, was unable to establish and maintain environments favorable to learning. Sarah reflected on her roles as a teacher and identified facilitating learning, management, and assessment as salient, each being associated with defining metaphors and belief sets. Sarah's efforts to improve her teaching began with the construction of a new metaphor, the social director,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 5 publications
0
59
0
6
Order By: Relevance
“…Over a decade of studies in teacher education have illustrated the influence of teachers' beliefs about teaching and learning on classroom practice (Artilles, 1996;Bowers & Flinders, 1990;Brickhouse, 1990;Briscoe, 1991;Bryan, 1997;Bryan & Abell, 1999;Clark & Peterson, 1986;Nespor, 1987;Pajares, 1992;Tobin & LaMaster, 1995). Hence, learning to provide "high-quality, diverse, and varied opportunities to learn science" must take into account the beliefs that teachers hold about issues of culture, race, ethnicity, class, gender, etc.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Over a decade of studies in teacher education have illustrated the influence of teachers' beliefs about teaching and learning on classroom practice (Artilles, 1996;Bowers & Flinders, 1990;Brickhouse, 1990;Briscoe, 1991;Bryan, 1997;Bryan & Abell, 1999;Clark & Peterson, 1986;Nespor, 1987;Pajares, 1992;Tobin & LaMaster, 1995). Hence, learning to provide "high-quality, diverse, and varied opportunities to learn science" must take into account the beliefs that teachers hold about issues of culture, race, ethnicity, class, gender, etc.…”
Section: )mentioning
confidence: 99%
“…Research has shown that knowing teachers' beliefs and designing instruction to explicitly confront those beliefs facilitate refinement of and/or transformation of beliefs and practices (Bryan & Abell, 1999;Harrington & Hathaway, 1995;Hollingsworth, 1989;Olmedo, 1997;Tobin & LaMaster, 1995). However, changes in beliefs of prospective teachers do not always translate into changes into practice.…”
Section: Implications For Research In Science Educationmentioning
confidence: 99%
“…Nor is there much evidence in the literature to suggest that teacher preparation programs explicitly guide preservice teachers to develop their conceptions of prior knowledge. Teacher education programs have begun to address preservice teachers' beliefs about students, teaching, and multicultural issues (Bryan & Abell, 1999;Bryan & Atwater, 2002;Hollingsworth, 1989;Tobin & LaMaster, 1995), all of which reinforce our need to gain a better understanding of how preservice teachers understand prior knowledge and its role in student learning. There seems to be an assumption that by simply stating to preservice teachers that prior knowledge is important means that they will believe it, and that they will know how to integrate it into their instructional practices.…”
Section: Introductionmentioning
confidence: 99%
“…The metaphors used in this language have shown themselves to be a means of articulating the thinking of the teaching community and of establishing 'bridges' between practical knowledge and the narrative that describes life in the classroom. They help to give an overall organization and articulation to a teacher's conceptions, roles, and practical knowledge, and allow one to discover the implicit referents that sustain the teacher and that have a powerful influence on his or her teaching behaviour in the classroom (Tobin and LaMaster 1995;BouJaoude 2000). There exist metaphors to define every educational environment.…”
Section: Models Of Conceptual Changementioning
confidence: 99%